Alumina carrier, preparation method of catalyst containing carrier and catalyst application
By using specific alumina support and metal components, a catalyst with high activity, high selectivity and high stability is formed, and the problems of existing catalysts in the dehydrogenation reaction of low-carbon alkanes are solved, and efficient and economical catalyst preparation and application are achieved.
Patent Information
- Application Number
- CN201811635858.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2018-12-29
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2038-12-29
AI Technical Summary
The existing catalysts are difficult to take into account the dehydrogenation activity, product selectivity, stability, regeneration properties, mechanical strength and preparation economy in the low-carbon alkane dehydrogenation reaction, resulting in rapid deactivation and carbon deposits of the catalyst under high temperature and high pressure conditions.
A catalyst with high activity, high selectivity and high stability is formed through a specific raw material ratio and preparation process. The alumina support consists of an aluminum source, starch, hexadecimal methyltetramine, urea and additives, and is prepared through stirring, molding, aging and high-temperature roasting. It combines metal components such as chloroplatinic acid, stannous chloride and potassium chloride to form an efficient dehydrogenation catalyst.
The catalyst exhibits high dehydrogenation activity and selectivity in the low-carbon alkane dehydrogenation reaction, excellent stability and regeneration performance, can maintain high efficiency performance during long-term operation, and has a low production cost.
Smart Images

Figure BDA0001930038430000101 
Figure BDA0001930038430000102 
Figure BDA0001930038430000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemistry, and in particular to an alumina carrier, a method for preparing a catalyst containing the carrier, and catalyst application. Background Art
[0002] Propylene and isobutylene are low-carbon olefins second only to ethylene in terms of usage, and are widely used. Propylene is mainly used to produce polypropylene, acrylonitrile, propylene oxide, acrylic acid, acrolein, etc., and isobutylene is mainly used to prepare methyl methacrylate, butyl rubber, polybutene, diisobutylene, etc. The industrial sources of propylene and isobutylene are mainly co-products or by-products of steam cracking and catalytic cracking. With the growing demand for low-carbon olefins, the propylene and isobutylene produced by these processes can hardly meet market demand. Dehydrogenation of low-carbon alkanes is an important way to increase the production of low-carbon olefins. According to the dehydrogenation process, it can be divided into oxidative dehydrogenation and direct dehydrogenation. Oxidative dehydrogenation requires the use of oxidants such as oxygen, which is a dangerous process and is prone to deep oxidation, reducing the yield of olefins. Direct dehydrogenation does not require an oxidant. Under the action of a catalyst, low-carbon alkanes can be highly selectively converted into corresponding olefins, while a large amount of hydrogen is produced as a by-product. Therefore, direct dehydrogenation has received widespread attention.
[0003] At present, direct dehydrogenation technologies include UOP's Oleflex process, ABB-Lummus's Catofin process, ConocoPhillips (Uhde)'s Star process, Snamprogetti / Yarsintz's FBD-4 process, Linde / BASF's PDH process, etc. Among the industrialized devices, Oleflex and Catofin processes have become mainstream processes, with the Oleflex process using platinum catalysts and the Catofin process using chromium catalysts.
[0004] Analysis of the prior art revealed that although the catalysts prepared by the prior art can exhibit certain performance under certain reaction conditions, aspects such as dehydrogenation activity, product selectivity, stability, regeneration performance, mechanical strength and preparation economy are often not taken into account at the same time.
[0005] The dehydrogenation of low-carbon alkanes is a highly endothermic reaction. It is limited by thermodynamic equilibrium and has harsh reaction conditions. Low pressure and high temperature are conducive to improving the yield of olefins, but too high temperature will aggravate the cracking and deep dehydrogenation of alkanes, resulting in a decrease in catalyst selectivity, accelerated carbon deposition, and rapid deactivation. Therefore, it is necessary to develop a dehydrogenation catalyst with high activity, high selectivity and high stability. Summary of the invention
[0006] The technical problem solved by the present invention is that the existing catalysts often cannot take into account the dehydrogenation activity, product selectivity, stability, regeneration performance, mechanical strength and preparation economy. Due to the nature of the dehydrogenation reaction of low-carbon alkanes, a dehydrogenation catalyst with high activity, high selectivity and high stability is studied.
[0007] In order to solve the above technical problems, a technical solution adopted in the present invention is: to provide an alumina carrier, the raw materials of the alumina carrier include: an aluminum source, starch, hexamethylenetetramine, urea, and an auxiliary agent, the auxiliary agent is selected from one or a mixture of methyl cellulose and ammonium bicarbonate, preferably methyl cellulose.
[0008] The aluminum source includes a mixture of one or more of pseudo-boehmite, gibbsite, and aluminum powder.
[0009] In the present invention, the alumina carrier raw material includes: 50-70 parts by mass of aluminum source, 2-5 parts by mass of starch, 3-6 parts by mass of hexamethylenetetramine, and 5-12 parts by mass of urea, preferably, 60 parts by mass of aluminum source, 3 parts by mass of starch, 4 parts by mass of hexamethylenetetramine, and 6 parts by mass of urea.
[0010] In the present invention, the methyl cellulose is 5 to 7 parts by mass, preferably 6 parts by mass.
[0011] The present invention also proposes a method for preparing a catalyst, which comprises the following steps:
[0012] ① Take aluminum source, starch, hexamethylenetetramine, urea, additives, add appropriate amount of deionized water and stir to form an alumina suspension, and continue stirring;
[0013] ② In step ①, add 10-40wt% nitric acid solution, preferably 25wt% nitric acid solution, at 30-60°C, preferably 45°C, and stir to form an alumina slurry;
[0014] ③ Drop alumina slurry into a mixture of one or more of liquid paraffin, vacuum pump oil, and transformer oil, preferably paraffin, and shape it at 60-100°C, preferably 85°C;
[0015] ④ The formed material is aged at 100-150°C for 4-20h, preferably at 120°C for 12h, washed with water, and dried at 100-150°C for 2-15h, preferably at 130°C for 8h;
[0016] ⑤ The dried material is heated to 960-1120°C and kept at a constant temperature for 6-10h, preferably at 1030°C and kept at a constant temperature for 4h. Before heating to 960-1120°C, preferably at 1030°C, it is kept at a constant temperature of 200-300°C, 400-500°C, 600-700°C and 800-900°C for 8-10h, preferably at 250°C, 450°C, 630°C and 850°C for 6h.
[0017] In the present invention, the raw materials of the catalyst include: the alumina carrier according to any one of claims 1 to 3, chloroplatinic acid, stannous chloride, and component one, wherein component one includes potassium chloride and zinc chloride or a mixture of both, preferably potassium chloride.
[0018] In the present invention, the raw materials of the catalyst include: 10 to 30 parts by mass of the alumina carrier described in any one of claims 1 to 3, 0.02 to 0.1 parts by mass of chloroplatinic acid, 0.02 to 0.1 parts by mass of stannous chloride, and 0.1 to 0.3 parts by mass of component one, preferably 20 parts by mass of the alumina carrier, 0.06 parts by mass of chloroplatinic acid, 0.07 parts by mass of stannous chloride, and 0.24 parts by mass of component one.
[0019] In the present invention, the method comprises the following steps:
[0020] ① Place the alumina carrier according to any one of claims 1 to 3 in a container, take 1.2 to 6 ml of a 0.01 to 0.05 g / ml chloroplatinic acid aqueous solution, 0.875 to 7 ml of a 0.01 to 0.08 g / ml stannous chloride aqueous solution, add 4 to 15.9 g of deionized water, preferably 6 ml of a 0.01 g / ml chloroplatinic acid aqueous solution, 1.4 ml of a 0.05 g / ml stannous chloride aqueous solution, and 10.6 g of deionized water to prepare an impregnation solution;
[0021] ② The pH value of the impregnation solution is adjusted to 0.35-1.45, preferably 0.65, and then the impregnation is performed, followed by vacuum drying at 60-100° C. for 3-10 hours, calcining at 400-700° C. for 4-8 hours, preferably vacuum drying at 80° C. for 5 hours, and calcining at 520° C. for 6 hours to obtain a precursor;
[0022] ③ Take 6-12 ml of potassium chloride solution containing 0.02-0.04 g / ml potassium, add 6-12 g of deionized water, adjust the pH value to 0.85-2.25, preferably take 8 ml of potassium chloride solution containing 0.03 g / ml potassium, add 10 g of deionized water, adjust the pH value to 1.25, impregnate the precursor at room temperature, then vacuum dry at 60-100°C for 3-10 h, calcine at 400-700°C for 4-8 h, preferably vacuum dry at 80°C for 5 h, and calcine at 520°C for 6 h to obtain the catalyst.
[0023] In the present invention, the catalyst is used for dehydrogenation of low-carbon alkanes, wherein the low-carbon alkanes are C1-C5 alkanes, and are further selected from one of propane, n-butane, isobutane, and pentane, or a mixture of two thereof.
[0024] In the present invention, the application conditions are: the volume ratio of hydrogen to low carbon alkane is 1:4 to 1:1, the reaction temperature is 450°C to 650°C, the pressure is normal pressure, and the mass space velocity of alkane is 3.0 to 6.0 h -1, preferably 3.5h -1 .
[0025] In the present invention, the reaction temperature is 610°C during propane dehydrogenation, and the reaction temperature is 590°C during isobutane dehydrogenation.
[0026] The catalyst of the present invention mainly has the following advantages:
[0027] 1. The catalyst of the present invention is suitable for dehydrogenating C1-C5 low-carbon alkanes to produce monoolefins. The catalyst has high dehydrogenation activity and selectivity, good operating stability and regeneration performance, slow activity decay, strong resistance to carbon deposition, and can be operated for a long time at a high single-pass conversion rate.
[0028] 2. The present invention uses mesoporous alumina with concentrated pore size distribution as the carrier. More than 90% of the carrier pore size is mesopores, there are no micropores, and the proportion of macropores is relatively small, which is conducive to the adsorption reaction of reactant molecules and the rapid desorption of products, shortens the contact time between products and metal active sites, and reduces the formation of carbon deposits. At the same time, the catalyst has good mechanical strength.
[0029] 3. The present invention does not introduce competitive adsorbents during the catalyst preparation process, does not require high-temperature steam treatment of the carrier or catalyst, improves the dispersibility of the metal components, avoids the aggregation of active metals, and reduces the catalyst preparation cost. DETAILED DESCRIPTION
[0030] Example 1
[0031] Preparation of carrier: Take 60g of pseudo-boehmite, 4g of starch, 4g of hexamethylenetetramine, 6g of urea, and 6g of methylcellulose, add appropriate amount of deionized water and stir to form a suspension with a mass content of 25% alumina, continue stirring for 2h, slowly add 15.5g of nitric acid solution with a mass concentration of 25%, and stir at 45°C for 2h to form an alumina sol slurry. Drop the alumina sol into a hot oil column with an oil phase of liquid paraffin at 85°C to form balls. Collect the formed balls at the lower end of the oil column, transfer them to an aging kettle and age them at 120°C for 12h, then wash with water and dry at 130°C for 8h. Place the dried formed carrier in a high-temperature furnace, increase the temperature to 1030°C at a heating rate of 1.5°C / min and keep it constant for 4h. Before increasing to 1030°C, keep it constant at 300°C, 450°C, 630°C and 850°C for 6h respectively to obtain. Alumina support beads A1, its physical properties are shown in Table 1.
[0032] Catalyst preparation: 20g of alumina carrier A1 was placed in a beaker, 6ml of 0.01g / ml platinum-containing chloroplatinic acid aqueous solution, 1.4ml of 0.05g / ml tin-containing stannous chloride aqueous solution, 10.6g of deionized water were added to prepare an impregnation solution, the pH value was adjusted to 0.65, the alumina carrier was impregnated at room temperature, then vacuum dried at 80°C for 5h, and calcined at 520°C for 6h to obtain a catalyst precursor containing platinum and tin. 8ml of 0.03g / ml potassium chloride solution was taken, 10g of deionized water was added, the pH value was adjusted to 1.25, the catalyst precursor was impregnated at room temperature, then vacuum dried at 80°C for 5h, and calcined at 520°C for 6h to obtain a finished catalyst A2 of 0.30% Pt-0.35% Sn-1.2% K.
[0033] Screening Example ①
[0034] Preparation of carrier: Take 60g of pseudo-boehmite, 4g of starch, 4g of hexamethylenetetramine, 6g of urea, and 6g of methylcellulose, add appropriate amount of deionized water and stir to form a suspension with a mass content of 25% alumina, continue stirring for 2h, slowly add 15.5g of nitric acid solution with a mass concentration of 25%, and stir at 45°C for 2h to form an alumina sol slurry. Drop the alumina sol into a hot oil column with an oil phase of liquid paraffin at 85°C to form balls. Collect the formed balls at the lower end of the oil column, transfer them to an aging kettle and age them at 120°C for 12h, then wash with water and dry at 130°C for 8h. Place the dried formed carrier in a high-temperature furnace, increase the temperature to 1030°C at a heating rate of 1.5°C / min and keep it at a constant temperature for 4h. Before increasing to 1030°C, keep it at a constant temperature for 6h at 200°C, 450°C, 630°C and 850°C respectively to obtain. Alumina carrier A1, its physical properties are shown in Table 1.
[0035] Catalyst preparation: 20g of alumina carrier A1 was placed in a beaker, 3ml of 0.02g / ml platinum-containing chloroplatinic acid aqueous solution, 4ml of 0.05g / ml tin-containing stannous chloride aqueous solution, 11g of deionized water were added, and the pH value was adjusted to 0.85. The alumina carrier was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 520°C for 6h to obtain a catalyst precursor containing platinum and tin. 8ml of potassium chloride solution containing 0.03g / ml potassium was taken, 10g of deionized water was added, the pH value was adjusted to 1.25, the catalyst precursor was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 520°C for 6h to obtain a finished catalyst A2-1 of 0.30% Pt-1.0% Sn-1.2% K.
[0036] Screening Example ②
[0037] Preparation of carrier: Take 60g of pseudo-boehmite, 4g of starch, 4g of hexamethylenetetramine, 6g of urea, and 6g of methylcellulose, add appropriate amount of deionized water and stir to form a suspension with a mass content of 25% alumina, continue stirring for 2h, slowly add 15.5g of nitric acid solution with a mass concentration of 25%, and stir at 45°C for 2h to form an alumina sol slurry. Drop the alumina sol into a hot oil column with an oil phase of liquid paraffin at 85°C to form balls. Collect the formed balls at the lower end of the oil column, transfer them to an aging kettle and age them at 120°C for 12h, then wash with water and dry at 130°C for 8h. Place the dried formed carrier in a high-temperature furnace, increase the temperature to 1030°C at a heating rate of 1.5°C / min and keep it constant for 4h. Before increasing to 1030°C, keep it constant at 300°C, 450°C, 630°C and 850°C for 6h respectively to obtain. Alumina carrier A1, its physical properties are shown in Table 1.
[0038] Catalyst preparation: 20 alumina carrier A1 is placed in a beaker, 2 ml of 0.03 g / ml platinum-containing chloroplatinic acid aqueous solution, 1.4 ml of 0.05 g / ml tin-containing stannous chloride aqueous solution, 15.6 g of deionized water are added to prepare an impregnation solution, the pH value is adjusted to 1.05, the alumina carrier is impregnated at room temperature, then vacuum dried at 80°C for 5 h, and calcined at 520°C for 6 h to obtain a catalyst precursor containing platinum and tin. 3 ml of 0.04 g / ml potassium chloride solution is taken, 15 g of deionized water is added, the pH value is adjusted to 2.05, the catalyst precursor is impregnated at room temperature, then vacuum dried at 80°C for 5 h, and calcined at 520°C for 6 h to obtain a finished catalyst A2-2 of 0.30% Pt-0.35% Sn-0.6% K.
[0039] Screening Example ③
[0040] Preparation of carrier: Take 60g of pseudo-boehmite, 4g of starch, 4g of hexamethylenetetramine, 6g of urea, and 6g of methylcellulose, add appropriate amount of deionized water and stir to form a suspension with a mass content of 25% alumina, continue stirring for 2h, slowly add 15.5g of nitric acid solution with a mass concentration of 25%, and stir at 45°C for 2h to form an alumina sol slurry. Drop the alumina sol into a hot oil column with an oil phase of liquid paraffin at 85°C to form balls. Collect the formed balls at the lower end of the oil column, transfer them to an aging kettle and age them at 120°C for 12h, then wash with water and dry at 130°C for 8h. Place the dried formed carrier in a high-temperature furnace, increase the temperature to 1030°C at a heating rate of 1.5°C / min and keep it constant for 4h. Before increasing to 1030°C, keep it constant at 300°C, 450°C, 630°C and 850°C for 6h respectively to obtain. Alumina carrier A1, its physical properties are shown in Table 1.
[0041] Catalyst preparation: 20 alumina carrier A1 is placed in a beaker, 1.5 ml of chloroplatinic acid aqueous solution containing 0.02 g / ml platinum, 1.4 ml of stannous chloride aqueous solution containing 0.05 g / ml tin, 15 g of deionized water are added to prepare an impregnation solution, the pH value is adjusted to 1.05, the alumina carrier is impregnated at room temperature, then vacuum dried at 80°C for 5 hours, and calcined at 520°C for 6 hours to obtain a catalyst precursor containing platinum and tin. 6 ml of potassium chloride solution containing 0.04 g / ml potassium is taken, 15 g of deionized water is added, the pH value is adjusted to 2.05, the catalyst precursor is impregnated at room temperature, then vacuum dried at 80°C for 5 hours, and calcined at 520°C for 6 hours to obtain a finished catalyst A2-3 of 0.15% Pt-0.35% Sn-1.2% K.
[0042] Example 2
[0043] Preparation of carrier: Take 30g of pseudo-boehmite, 30g of gibbsite, 4g of ammonium bicarbonate, 6g of starch, 4g of hexamethylenetetramine, and 10g of urea, add appropriate amount of deionized water and stir to form a suspension with a mass content of 30% alumina, continue stirring for 2h, slowly add 12.5g of nitric acid solution with a mass concentration of 30%, and stir at 45℃ for 2h to form alumina sol slurry. Drop the alumina sol into a hot oil column with a 95℃ oil phase of vacuum pump oil to form balls. Collect the formed balls at the lower end of the oil column, transfer them to an aging kettle, age them at 150℃ for 12h, then wash them with water and dry them at 130℃ for 8h. Place the dried formed carrier in a high-temperature furnace, raise the temperature to 1100℃ at a heating rate of 1.0℃ / min and keep it constant for 4h. Before rising to 1100℃, keep it constant at 250℃, 450℃, 680℃ and 880℃ for 6h respectively to obtain Alumina carrier B1, its physical properties are shown in Table 1.
[0044] Catalyst preparation: Take carrier B1 and prepare a catalyst according to the method of Example 1. A finished catalyst B2 of 0.30% Pt-0.25% Sn-1.2% K is obtained.
[0045] Example 3
[0046] Preparation of carrier: Take 60 grams of aluminum powder (10 mesh), add 500 ml of hydrochloric acid solution with a mass concentration of 25%, dissolve the aluminum powder at 45°C, add 12 grams of polyacrylamide, 6 g of hexamethylenetetramine, 12 grams of urea, and an appropriate amount of deionized water, and continue stirring to form an aluminum sol with an aluminum oxide mass content of 30%. Drop the alumina sol into a hot oil column with a 95°C oil phase of transformer oil to form balls. Collect the molded small balls at the lower end of the oil column, transfer them to an aging kettle, age them at 150°C for 12 hours, then wash them with water, and dry them at 130°C for 8 hours. Place the dried molded carrier in a high-temperature furnace, raise the temperature to 1150°C at a heating rate of 2.0°C / min and keep it at a constant temperature for 4 hours. Before rising to 1150°C, keep it at a constant temperature of 250°C, 500°C, 700°C and 900°C for 6 hours respectively to obtain. Alumina carrier C1, its physical properties are shown in Table 1.
[0047] Catalyst preparation: 20g of alumina carrier C1 was placed in a beaker, 6ml of 0.01g / ml platinum-containing chloroplatinic acid aqueous solution was taken, 11.6g of deionized water was added to prepare an impregnation solution, the pH value was adjusted to 0.85, the alumina carrier was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 450°C for 6h to obtain a catalyst precursor containing platinum. 1.4ml of 0.05g / ml tin-containing stannous chloride aqueous solution was taken, 11.0g of deionized water was added to prepare an impregnation solution, the pH value was adjusted to 1.25, the platinum-containing catalyst precursor was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 500°C for 6h to obtain a catalyst precursor containing platinum and tin. Take 12 ml of potassium chloride solution containing 0.02 g / ml potassium, add 6.9 g of deionized water, adjust the pH value to 1.55, impregnate the catalyst precursor at room temperature, then vacuum dry at 80°C for 5 hours, and calcine at 520°C for 6 hours to obtain the finished catalyst C2 with 0.30% Pt-0.35Sn%-1.2K%.
[0048] Example 4
[0049] Preparation of carrier: Alumina carrier D1 was prepared according to the method of Example 1, except that the final calcination temperature of the carrier was 1000° C. Its physical properties are shown in Table 1.
[0050] Catalyst preparation: 20g of alumina carrier D1 was placed in a beaker, 6ml of 0.01g / ml platinum-containing chloroplatinic acid aqueous solution, 1.4ml of 0.05g / ml tin-containing stannous chloride aqueous solution, 10.6g of deionized water were added to prepare an impregnation solution, the pH value was adjusted to 0.85, the alumina carrier was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 520°C for 6h to obtain a catalyst precursor containing platinum and tin. 10ml of potassium chloride solution containing 0.02g / ml potassium, 1.8ml of zinc chloride solution containing 0.05g / ml zinc, 5g of deionized water were added, the pH value was adjusted to 1.55, the catalyst precursor was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 520°C for 6h to obtain a finished catalyst D2 of 0.30% Pt-0.35% Sn-1.0% K-0.45% Zn.
[0051] Example 5
[0052] Preparation of carrier: an alumina carrier was prepared according to the method of Example 1, except that a stannous chloride solution was added to the aluminum sol before drop ball molding to obtain alumina carrier beads E1 with a final tin content of 0.35%. Its physical properties are shown in Table 1.
[0053] Catalyst preparation: 20g of alumina carrier E1 was placed in a beaker, 6ml of 0.01g / ml platinum-containing chloroplatinic acid aqueous solution was taken, 12.6g of deionized water was added, and the impregnation solution was prepared. The pH value was adjusted to 0.85, and the tin-containing alumina carrier was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 550°C for 6h to obtain a catalyst precursor containing platinum and tin. 12ml of 0.02g / ml potassium chloride solution was taken, 6g of deionized water was added, the pH value was adjusted to 1.25, and the catalyst precursor was impregnated at room temperature, and then vacuum dried at 80°C for 5h, and calcined at 550°C for 6h to obtain a finished catalyst E2 of 0.30% Pt-0.35% Sn-1.2% K.
[0054] Comparative Example 1
[0055] Preparation of carrier: The carrier aluminum oxide F1 was prepared according to the method of Example 1, except that the temperature was directly raised to 1030°C at a heating rate of 1.5°C. Then, it was treated at 850°C for 10 hours in air containing 10% (volume ratio) water vapor. Its physical properties are shown in Table 1.
[0056] Catalyst preparation: Take carrier F1 and prepare a catalyst according to the method of Example 1 to obtain a finished catalyst F2 with 0.30% Pt-0.35% Sn-1.2% K.
[0057] Comparative Example 2
[0058] Preparation of carrier: The tin-containing alumina carrier G1 was prepared according to the method of Example 5. The difference is that the carrier calcination procedure is: first calcined in an air atmosphere at 650°C for 4 hours, then treated in air containing 5% (volume ratio) water vapor at 650°C for 10 hours, and finally heated to 1100°C and calcined in an air atmosphere for 4 hours. Its physical properties are shown in Table 1.
[0059] Catalyst preparation: Take carrier G1 and prepare a catalyst according to the method of Example 5 to obtain a finished catalyst G2 with 0.30% Pt-0.30% Sn-1.2% K.
[0060] Comparative Example 3
[0061] Carrier preparation: An alumina carrier was prepared according to the method of Example 1, except that the alumina pellets were dried and calcined at 750°C for 6 h to obtain an alumina carrier H1, whose physical properties are shown in Table 1.
[0062] Catalyst preparation: Take carrier H1 and prepare a catalyst according to the method of Example 1 to obtain a finished catalyst H2 with 0.30% Pt-0.35% Sn-1.2K%.
[0063] Example 6
[0064] Dehydrogenation performance evaluation: The dehydrogenation performance evaluation of fresh catalyst and regenerated catalyst was carried out in a quartz tube fixed bed reactor with 5 g of catalyst loaded. Reaction conditions: pressure 0.2 MPa, H2 / CnH2n+2 = 1 / 1 (volume ratio), alkane mass space velocity 3.5 h -1 The reaction temperature for propane dehydrogenation was 610°C, and the reaction temperature for isobutane dehydrogenation was 590°C. Before the catalyst evaluation, it was reduced at 550°C for 3h in a hydrogen atmosphere in a reaction tube.
[0065] The product gas composition was analyzed online every hour using a Shimadzu GC-2014C gas chromatograph (alumina capillary column, 50 m×0.53 mm×15 μm, FID detector) to calculate the alkane conversion and olefin selectivity.
[0066] Catalyst regeneration: After the catalyst is deactivated, it is unloaded from the reactor and regenerated in a tubular furnace under air atmosphere. Regeneration conditions: air flow rate 100 ml / min, temperature 550°C, regeneration time 4 h.
[0067] The catalyst evaluation results are shown in Table 2, Table 3 and Table 4.
[0068] Catalyst carbon deposition test: The evaluated catalyst was unloaded from the reactor, sieved, placed in a drying oven at 120°C for 5 hours, and weighed, recorded as W1, and then placed in a tubular furnace in an air atmosphere at 550°C for 4 hours and weighed, recorded as W2. Catalyst carbon deposition rate % = (W1-W2) / W1*100. As can be seen from Tables 2 to 4, the catalyst of the present invention has higher alkane dehydrogenation activity and selectivity, and compared with the comparison agent, it has better operating stability, slower deactivation rate, and lower coking amount, indicating that the catalyst of the present invention has better reaction performance.
[0069] During catalysis, the volume ratio of hydrogen to low carbon alkane is 1:4 to 1:1, the reaction temperature is 450℃ to 650℃, the pressure is normal pressure, and the mass space velocity of alkane is 3.0 to 6.0h -1 .
[0070] Table 1 Physical properties of carrier
[0071]
[0072] Table 2 Catalyst propane dehydrogenation performance
[0073]
[0074]
[0075] Table 3 Catalyst isobutane dehydrogenation performance
[0076]
[0077] Table 4 Regeneration performance of catalyst A2
[0078]
[0079] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An alumina carrier, characterized in that The raw materials of the alumina carrier include: 50-70 parts by weight of aluminum source, 2-5 parts by weight of starch, 3-6 parts by weight of hexamethylenetetramine, 5-12 parts by weight of urea, and the auxiliary agent is selected from methyl cellulose, which is 5-7 parts by weight; The carrier was prepared by the following method: ① Take aluminum source, starch, hexamethylenetetramine, urea, additives, add deionized water and stir to form an alumina suspension, and continue stirring; ② Add 10-40wt% nitric acid solution in step ①, stir at 30-60°C to form an alumina slurry; ③ Drop alumina slurry into a mixture of one or more of liquid paraffin, vacuum pump oil, and transformer oil, and form it at 60-100°C; ④Age the formed material at 100~150℃ for 4~20h, wash with water, and dry at 100~150℃ for 2~15h; ⑤ Raise the temperature of the dried material to 960~1120℃ and keep it constant for 6~10h. Before raising the temperature to 960~1120℃, keep it constant at 200~300℃, 400~500℃, 600~700℃ and 800~900℃ for 8~10h respectively.
2. The alumina carrier according to claim 1, characterized in that The raw materials of the alumina carrier include: 60 parts by mass of an aluminum source, 4 parts by mass of starch, 4 parts by mass of hexamethylenetetramine, and 6 parts by mass of urea.
3. The alumina carrier according to claim 1, characterized in that The amount of methylcellulose was 6 parts by mass.
4. The method for preparing the alumina carrier according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: ① Take aluminum source, starch, hexamethylenetetramine, urea, additives, add deionized water and stir to form an alumina suspension, and continue stirring; ② Add 10-40wt% nitric acid solution in step ①, stir at 30-60°C to form an alumina slurry; ③ Drop alumina slurry into a mixture of one or more of liquid paraffin, vacuum pump oil, and transformer oil, and form it at 60-100°C; ④Age the formed material at 100~150℃ for 4~20h, wash with water, and dry at 100~150℃ for 2~15h; ⑤ Raise the temperature of the dried material to 960~1120℃ and keep it constant for 6~10h. Before raising the temperature to 960~1120℃, keep it constant at 200~300℃, 400~500℃, 600~700℃ and 800~900℃ for 8~10h respectively.
5. The method for preparing an alumina carrier according to claim 4, characterized in that: Step ② is to add 25wt% nitric acid solution in step ①, and stir at 45°C to form an alumina slurry; In step ③, forming at 85°C; In step ④, the formed material is aged at 120° C. for 12 h, washed with water, and dried at 130° C. for 8 h; In step ⑤, the dried material is heated to 1030°C and kept at this temperature for 4 hours. Before heating to 1030°C, the dried material is kept at 250°C, 450°C, 630°C and 850°C for 6 hours respectively.
6. A catalyst containing an alumina carrier, characterized in that The raw materials of the catalyst include: the alumina carrier according to any one of claims 1 to 3, chloroplatinic acid, stannous chloride, and component one, wherein the component one includes potassium chloride and zinc chloride or a mixture of both.
7. The catalyst according to claim 6, characterized in that Component one is selected from potassium chloride.
8. The catalyst according to claim 6, characterized in that The raw materials of the catalyst include: 10-30 parts by weight of the alumina carrier according to any one of claims 1 to 3, 0.02-0.1 parts by weight of chloroplatinic acid, 0.02-0.1 parts by weight of stannous chloride, and 0.1-0.3 parts by weight of component 1.
9. The catalyst according to claim 8, characterized in that The raw materials of the catalyst include: 20 parts by mass of an alumina carrier, 0.06 parts by mass of chloroplatinic acid, 0.07 parts by mass of stannous chloride, and 0.24 parts by mass of component one.
10. The method for preparing the catalyst according to any one of claims 6 to 9, characterized in that: The preparation method comprises the following steps: ① Place the alumina carrier according to any one of claims 1 to 3 in a container, take 1.2 to 6 ml of a chloroplatinic acid aqueous solution containing 0.005 to 0.05 g / ml of platinum, 0.875 to 7 ml of a stannous chloride aqueous solution containing 0.01 to 0.08 g / ml of tin, and add 4 to 15.9 g of deionized water to prepare an impregnation solution; ② The pH value of the impregnation solution is adjusted to 0.35-1.45, and then the impregnation is performed, followed by vacuum drying at 60-100°C for 3-10 hours, and calcination at 400-700°C for 4-8 hours to obtain a precursor; ③ Take 6-12 ml of potassium chloride solution containing 0.02-0.04 g / ml potassium, add 6-12 g of deionized water, adjust the pH value to 0.85-2.25, impregnate the precursor at room temperature, then vacuum dry at 60-100°C for 3-10 hours, and calcine at 400-700°C for 4-8 hours to obtain the catalyst.
11. The preparation method according to claim 10, characterized in that: In step ①, 6 ml of 0.01 g / ml chloroplatinic acid aqueous solution containing platinum, 1.4 ml of 0.05 g / ml stannous chloride aqueous solution containing tin, and 10.6 g of deionized water are added; In step ②, the pH value is adjusted to 0.65, vacuum dried at 80°C for 5h, and calcined at 520°C for 6h; In step ③, 8 ml of potassium chloride solution containing 0.03 g / ml potassium is added with 10 g of deionized water, the pH value is adjusted to 1.25, vacuum dried at 80° C. for 5 h, and calcined at 520° C. for 6 h.
12. Use of the catalyst according to any one of claims 6 to 9, characterized in that: The catalyst is used for dehydrogenation of low-carbon alkanes, which are C1-C5 alkanes.
13. Use of the catalyst according to claim 12, characterized in that: The low carbon alkane is selected from one of propane, n-butane, isobutane and pentane or a mixture of two of them.
14. Use of the catalyst according to claim 12, characterized in that: The application conditions are: a volume ratio of hydrogen to low carbon alkane of 1:4 to 1:1, a reaction temperature of 450°C to 650°C, a pressure of normal pressure, and a mass space velocity of alkane of 3.0 to 6.0 h -1 .
15. Use of the catalyst according to claim 14, characterized in that: Alkane mass space velocity 3.5h -1 .
16. Use of the catalyst according to claim 14, characterized in that: The reaction temperature is 610°C for propane dehydrogenation and 590°C for isobutane dehydrogenation.
Citation Information
Patent Citations
Selective catalyst system for oxidative dehydrogenation of alkanes
WO2018025117A1
Alumina carrier and preparation method thereof
CN105312091A
Preparation method for carrier of low density, large void content and high intensity aluminium oxide
CN1068975A